PENGARUH TINGKAT PENGGUNAAN MEDIA SOSIAL DAN MOTIVASI TERHADAP MINAT BERWIRAUSAHA PADA MAHASISWA PROGRAM STUDI MANAJEMAN PERGURUAN TINGGI DI KOTA DENPASAR - Sumerta, I Komang; Redianingsih, Ni Komang; Pranawa, I Made Baji; Indahyani, Desak Nyoman Tri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.09.NO.07.TAHUN 2020, 2020)
The role of social media is increasingly recognized in boosting business or brand performance. Developing creativity in entrepreneurship among students with the use of social media is a positive impact on the use of social media itself. The purpose of this study was to determine the level of use of social media and motivation towards entrepreneurship interests. This research was conducted at the College of Management Study Program located in the city of Denpasar. The sample used was as many as 100 people or about 90% of the total active students of management courses in high schools in the city of Denpasar. Data analysis techniques used are Multiple Linear Regression Analysis, Determination Coefficient, F Test and t Test. The results of analysis in this study indicate the level of use of Social Media has a positive and partially significant effect on Entrepreneurial Interest, it can be seen from the t-value of the variable Organizational Commitment is 8.417 is greater than the t-table value of 1.661. Motivation has a positive and partially significant effect on Entrepreneurial Interest, it can be seen from the t-count value of Organizational Culture variables is 5.736 greater than the t-table value of 1.661.